Jogos entre imagem e palavra: processos de criação de escritores visuais - Kahan, Mara Paulete Herbst (2019)
This work investigates, within the literature dedicated to children and youth, the process of creating visual texts produced by the interaction between the writer and the visual writer, between word and image, considering the intentionality of this process, and the power of communication in the construction of narrative and image as cultural mediation. Exploratory questions are addressed: how is the creative and collaborative process between word and image? How does this narrative and visual creation interact? What are the motivations and challenges of this artistic making trajectory? As a artist, teacher, art educator and art therapist, understanding these processes in productions aimed primarily at children and young people, but also reaching readers of other age groups, can resonate and expand the power of art teaching in their interdisciplinary connections. Data were collected through semi-structured, recorded and transcribed interviews, conducted with two visual writers, Fernando Pires and Odilon Moraes. The writer Edith Chacon, who produces works together with Fernando Pires, was also interviewed. Odilon Moraes also relates the process of creating his works together with the writer Carolina Moreyra. The interviews and their analysis were conducted from a methodological perspective based on exploratory case studies, under the light of theoretical references